Culinary Business Online Marketing Strategies in the Post-Covid 19 Pandemic Era - Wahyudin Rahman (International Journal Labs, 2023)
The Covid-19 pandemic has had a major impact on the culinary industry in Indonesia, especially on small and medium enterprises. Many culinary business actors have been forced to close their businesses because they are affected by the pandemic. The purpose of this study is to analyze and examine the phenomana and symptoms of online product marketing by culinary business people in Jakarta in the midst of the Covid-19 pandemic that has hit Indonesia, especially in Jakarta. The research method used is a qualitative approach by conducting direct observations, literature studies and in-depth interviews with key informants as business actors and microeconomic observers. Analysis and discussion of observations of the phenomena and symptoms of online marketing Culinary Sales in Jakarta shows that online culinary marketing has experienced a significant increase in income. Theoretically, marketing online product sales is the most appropriate strategy, both in the midst of the Covid-19 pandemic and in the midst of normal conditions. The conclusion of the results of this study is that online product marketing today and in the future is the best choice for middle to lower economic actors who are difficult to avoid.